Development Of Santri Moral Reasoning (Study At Pesantren Al Ihya 'Ulumaddin Kesugihan-Cilacap) - Ali, Musyafa; Toifur, Toifur; Hasbullah, Ahsan (International Journal of Scientific Research and Management (IJSRM), 2022)
Reality shows that learning has only been limited to teaching, not yet aimed at improvement, enrichment activities, increased learning motivation, and the development of effective learning attitudes and habits. In the process of education these three domains should receive balanced attention so as to produce quality graduates. This study aims to describe and analyze the development of moral reasoning in pesantren. The approach used in this study cannot be separated from the research objective, which is to describe the development of students' moral reasoning. To explore the data researchers used observation, interview, and documentation techniques. While in determining respondents, researchers used a purposive sampling technique. This technique is a technique for determining the sample with certain considerations or criteria. As for the respondents in this study are the caregivers of the pesantren, boarding kyai boarding school, head of the boarding school, and Santri. Data analysis techniques use the stages of data reduction, data presentation, and data verification. The results of the study showed that the moral reasoning of the santri was done through hasanah mau'idzah, uswah hasanah, and hasanah da'wah. Mau'idzah hasanah is done by a nurse, a kyai council, and a cleric through the study of the yellow book, the study of Selasan, and briefings. Uswah hasanah is performed by caregivers, clerics, and religious teachers to strengthen knowledge about morals / morals. The proselytizing of hasanah is done by the santri and the kyai by means of respect to Allah SWT. These three activities can be mapped into outward efforts (dzahiran) and inner efforts (inner).